Risk Aversion and COVID-19 Vaccine Hesitancy - Anthony Lepinteur; Liyousew G. Borga; Andrew E. Clark; Claus Vögele; Conchita D'Ambrosio (Institute of Labor Economics (IZA), 2023)
We here investigate the role of risk aversion in COVID-19 vaccine hesitancy. The theoretical effect is ambiguous, as both COVID-19 infection and vaccination side-effects involve probabilistic elements. In large-scale data covering five European countries, we find that vaccine hesitancy falls with risk aversion, so that COVID-19 infection is perceived as involving greater risk than is vaccination.
Keywords: I12; D81; 330; risk aversion; COVID-19; vaccine hesitancy